2015
DOI: 10.1007/s00192-015-2790-x
|View full text |Cite
|
Sign up to set email alerts
|

MRI of female urethra and periurethral pathologies

Abstract: We provide a comprehensive review of normal MR anatomy of the female urethra, as well as the MR features of practically important urethral and periurethral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 32 publications
1
22
0
Order By: Relevance
“…Periurethral glands are located in the posterolateral aspect of the distal two-thirds of the urethra. The location of the most urethral diverticula corresponds to the location of the periurethral glands, further supporting the theory of formation of diverticula in patients with infected and obstructed periurethral glands (44).…”
Section: Urethral Diverticulumsupporting
confidence: 72%
See 1 more Smart Citation
“…Periurethral glands are located in the posterolateral aspect of the distal two-thirds of the urethra. The location of the most urethral diverticula corresponds to the location of the periurethral glands, further supporting the theory of formation of diverticula in patients with infected and obstructed periurethral glands (44).…”
Section: Urethral Diverticulumsupporting
confidence: 72%
“…Skene Gland Cysts.-Skene gland cysts are cysts of Skene (periurethral) ducts, which are tubuloalveolar structures located in the posterolateral aspect of the distal two-thirds of the urethra. The largest and most caudally located periurethral glands are called Skene glands (44). The glands secrete mucus and have ducts that drain directly into the urethral lumen.…”
Section: Urethral Diverticulummentioning
confidence: 99%
“…Unenhanced T1-weighted and T2-weighted MRI images were obtained. A suburethral mass was diagnosed if a mass lesion was present and located posterolateral to the urethra 14 . The two perpendicular diameters of the mass were measured in mm in the axial and sagittal planes, and the largest diameter of the mass was used in the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, Gakis et al [30] reported one case (0.9%) of secondary bladder cancer 41 mo after initial therapy for PUC. Enlarged regional lymph nodes (LNs) are likely to represent metastatic disease (84%), making assessment of disease extent with pelvic magnetic resonance imaging for local staging obligatory [13,31,32]. Additionally, LN biopsy is proposed by the NCCN as well.…”
Section: Diagnostic Evaluation and Stagingmentioning
confidence: 99%